Robust reliabile H∞ control for uncertain systems with pole constraints - Gao, X.; Teo, Kok Lay; Duan, G.; Wang, N. (ICIC International, 2012)
This paper investigates the robust reliable H-infinity control for uncertain systems. The system under consideration is subject to parameter uncertainties, external disturbances, actuator faults and pole constraints. A reliable output feedback controller is designed via a Lyapunov function approach in such a way that the closed-loop system will satisfy the system design requirements. The existence conditions for the admissible controller are given in terms of linear matrix inequalities (LMIs). The controller design is thus transformed into a convex optimization problem subject to LMI constraints. Two illustrative examples are provided to show the effectiveness of the proposed control design method.